Analysis of business models innovation: A multiple case study - Moema Pereira Nunes; Ana Paola Russo (Innovation & Management Review, 2019)
Purpose: This paper aims to analyze the business model innovation in medium and large Brazilian manufacturing companies located in Rio do Sul State. Design/methodology/approach: A holistic multiple case study in five companies was developed. Data were collected through interviews and analyzed according to the content analysis technique. Findings: The main motivation to business model innovation was the innovation in products and services, while the difficulties were the factors relating to the cost. The most common practice among cases was innovation in value proposition and the most widely used method was learning-by-searching. While part of the theory was demonstrated in the case studies, new motivations and practices were identified. The investigation of the learning process on business models' innovation is pioneered in this study. Further studies on this subject are required. Originality/value: New business models are likely to provide new opportunities to better address customer needs, generating differentiating itself from its competitors. It is a subject little investigated in the international context, and there are no studies to investigate the experience of Brazilian companies.
Keywords: 650; Innovation; Motivations; Learning; Business models; Difficulties